Ipsilateral internal carotid artery web and acute ischemic stroke: A cohort study, systematic review and meta-analysis. - Brian Mac Grory (Public Library of Science (PLoS), 2021)
Introduction The carotid web is a compelling potential mechanism of embolic ischemic stroke. In this study, we aim to determine the prevalence of ipsilateral carotid web in a cohort of ischemic stroke patients and to perform a systematic review and meta-analysis of similar cohorts. Patients & methods We performed a retrospective, observational, cohort study of acute ischemic stroke patients admitted to a comprehensive stroke center from June 2012 to September 2017. Carotid web was defined on computed tomography angiography (CTA) as a thin shelf of non-calcified tissue immediately distal to the carotid bifurcation. We described the prevalence of carotid artery webs in our cohort, then performed a systematic review and meta-analysis of similar cohorts in the published literature. Results We identified 1,435 potentially eligible patients of whom 879 met criteria for inclusion in our analysis. An ipsilateral carotid web was detected in 4 out of 879 (0.45%) patients, of which 4/4 (1.6%) were in 244 patients with cryptogenic stroke and 3/4 were in 66 (4.5%) patients <60 years old with cryptogenic stroke. Our systematic review yielded 3,192 patients. On meta-analysis, the pooled prevalence of ipsilateral carotid web in cryptogenic stroke patients <60 was 13% (95% CI: 7%-22%; I2 = 66.1%). The relative risk (RR) of ipsilateral versus contralateral carotid web in all patients was 2.5 (95% CI 1.5-4.2, p = 0.0009) whereas in patients less than 60 with cryptogenic stroke it was 3.0 (95% CI 1.6-5.8, p = 0.0011). Discussion Carotid webs are more common in young patients with cryptogenic stroke than in other stroke subtypes. Future studies concerning the diagnosis and secondary prevention of stroke associated with carotid web should focus on this population.